Enhanced nitrate removal in an Fe0-driven autotrophic denitrification system using hydrogen-rich water. Issue 8 (5th July 2019) - Zhu, Tingting; Cai, Weiwei; Wang, Bo; Liu, Wenzong; Feng, Kai; Deng, Ye; Wang, Aijie
Abstract : Autotrophic denitrification can be driven using zero valent iron (ZVI) as an electron donor. Abstract : Autotrophic denitrification can be driven using zero valent iron (ZVI) as an electron donor. Balancing the competitive reactions of abiotic nitrate removal and biotic nitrate removal by H2 is the key problem for iron-assisted autotrophic denitrification. Hence, H2 production by ZVI corrosion plays an important role in the iron-assisted nitrate reduction process, which determines the nitrate reduction rate and the end product. However, few studies concentrate on the effect of soluble H2 on ZVI corrosion and the performance of iron-assisted autotrophic denitrification. A hydrogen-rich solution is obtained by dual-chamber MFCs, which is usually directly discarded. The present study aimed to demonstrate that the dissolved hydrogen can be feasibly applied in iron-assisted autotrophic denitrification to accelerate nitrate reduction during ZVI corrosion. It was observed that a continuous dissolved hydrogen supply via electrolysis promoted and stabilized the performance of iron-assisted autotrophic denitrification. The average nitrate removal was 47.3% ± 0.2% in ZVI reactors with dissolved hydrogen-rich water (DH reactors), and 30.2% ± 0.3% in ZVI reactors without dissolved hydrogen-rich water (control reactors). Moreover, the concentration of nitrite was 0.04 mg L −1 in the DH reactors compared with 0.50 mg L −1 in the control reactors. No other intermediates ( e.g. N2 O) were found in both the autotrophic denitrification reactors. Finally, the hydrogen-rich water enriched the denitrifying bacteria and increased the abundance of specific functional genes, resulting in the promotion of hydrophobic denitrification during the iron-assisted nitrate removal.